I have a nine digits positive integer which shows the following property 9 × d 1 d 2 d 3 ⋯ d 8 d 9 = d 9 d 8 d 7 ⋯ d 2 d 1 that is when it's multiplied by 9, the digits are reversed. Find the largest reversed number .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
The equation in the problem should be 9 × d 1 d 2 d 3 ⋯ d 8 d 9 = d 9 d 8 d 7 ⋯ d 2 d 1 .
Problem Loading...
Note Loading...
Set Loading...
The general formula for such n digits number can be written as 9 9 ( 1 0 n − 2 − 1 ) Set n = 9
The answer is 1 1 ⋅ ( 1 0 7 − 1 ) ⋅ 9 = 9 8 9 9 9 9 9 9 0 1 .
Additional facts 9 9 ( 1 0 n − 2 − 1 ) − 1 1 ( 1 0 n − 2 − 1 ) = 8 8 ( 1 0 n − 2 − 1 ) = 8 ⋅ 1 1 ( 1 0 n − 2 − 1 ) , n > 3
Generalization: Let us try to figure out the smallest possible number such × b 0 b n b 1 ⋯ b n − 1 b n − 1 ⋯ b 1 b n 9 b 0 For a single digit number 9 ⋅ b 0 = b 0 ⟹ b 0 = 0 . On the similar manner we can observe that for two and three digit number ⎩ ⎪ ⎨ ⎪ ⎧ 9 ( 1 0 b 0 + b 1 ) = 1 0 b 1 + b 0 ⇒ 8 9 b 0 = 9 0 b 1 9 ( 1 0 0 b 0 + 1 0 b 1 + b 2 ) = 1 0 0 b 2 + 1 0 b 1 + b 0 ⇒ 8 9 9 b 0 + 8 0 b 1 = 9 1 b 2 For the above two cases we cannot find such b 0 , b 1 , b 2 ∈ Z + < 1 0 . Trying for the 4 digit number we can observe that 8 9 9 9 b 0 + 8 9 0 b 1 − 1 0 b 2 − 9 9 1 b 3 = 0 Clearly b 0 = 1 implying b 3 = 9 from above cryptogram set and 8 9 0 b 1 − 1 0 b 2 = − 8 0 and hence we obtain b 1 = 0 , b 2 = 8 and 1 0 8 9 our smallest number.
Note that 1 1 ⋅ 9 9 = 1 1 ( 1 0 4 − 2 − 1 ) = 1 0 8 9 1 1 ⋅ 9 9 9 = 1 1 ( 1 0 5 − 3 − 1 ) = 1 0 9 8 9 1 1 ⋅ 9 9 9 9 = 1 1 ( 1 0 6 − 4 − 1 ) = 1 0 9 9 8 9 from the above pattern 1 1 ( 1 0 n − 2 − 1 ) , we can easily determine the smallest nth digit number for n ≥ 4 such property holds true. For 5 digit such number we set n = 5 giving us 1 0 9 8 9 . Reversing the digit we further observe that 9 8 0 1 9 8 9 0 1 9 8 9 9 0 1 = 9 9 ⋅ 9 9 = 9 9 ( 1 0 4 − 2 − 1 ) = 9 9 ⋅ 9 9 9 = 9 9 ( 1 0 5 − 2 − 1 ) = 9 9 ⋅ 9 9 9 9 = 9 9 ( 1 0 6 − 2 − 1 ) And we have then 9 9 ⋅ ( 1 0 n − 2 − 1 ) ÷ 1 1 ( 1 0 n − 2 − 1 ) = 9 . If we perform the subtraction we can observe that 9 9 ( 1 0 n − 1 ) − 1 1 ( 1 0 n − 1 ) = 8 8 ( 1 0 n − 2 − 1 ) = 8 ⋅ 1 1 ( 1 0 n − 2 − 1 ) set n = 2 , 3 , 4 , ⋯ then 8 ⋅ 1 1 ( 1 0 4 − 2 − 1 ) = 8 7 1 2 8 ⋅ 1 1 ( 1 0 5 − 2 − 1 ) = 8 7 9 1 2 8 ⋅ 1 1 ( 1 0 6 − 2 − 1 ) = 8 9 9 7 1 2 On reversing these numbers we can find the general formula 2 ⋅ 1 0 8 9 = 2 ⋅ 1 1 ( 1 0 n − 2 − 1 ) and hence 8 ⋅ 1 1 ( 1 0 n − 2 − 1 ) ÷ 2 ⋅ 1 1 ( 1 0 n − 2 − 1 ) = 4 .
I had set up a problem upon these amazing number few weeks ago here Reflection .